CUKAI PLASTIK UNTUK MENGATASI INDONESIA DARURAT SAMPAH PLASTIK - Jesly Panjaitan (Pusat Kajian Anggaran, 2019)
Indonesia has a significant problem with plastic. The purpose of this study is to analyze Indonesia’s problems with plastic and analize the impact of the plastic waste. The excise of plastic is not implemented yet due to polemic between two ministries and the absence of implementing regulations of plastic excise. It is needed courage and willpower from Government to implement the excise of plastic. The policy should combine with other fiscal policies and need participation of various parties instead of government only